Comparison of PechaKucha and traditional PowerPoint presentations in nursing education: A randomized controlled study - Bakcek, Ozgu; Tastan, Sevinc; Iyigun, Emine; Kurtoglu, Pervin; Tastan, Birhan (Elsevier Sci Ltd, 2020)
This study aims to compare the effects of PechaKucha and traditional PowerPoint presentations on the learning performance of nursing students. This randomized controlled trial study was conducted in March 2016 at a nursing school in Ankara, Turkey. The participants were randomly distributed to the intervention group, which received a lecture using the PechaKucha presentation method (n = 66), and to the control group, which received a lecture using the traditional PowerPoint presentation (n = 68). The subject, Knee Prosthesis and Nursing Approaches, was given to both groups in different classrooms at the same time. The efficiency of the presentation methods was evaluated by a test on the content of the lecture. Satisfaction levels of the participants were evaluated by using the Visual Analogue Scale. There was no statistically significant relationship between the average test results of the groups. The satisfaction levels of the participants in the intervention group was higher than the control group (p < 0.01). This study showed that, although there was no difference between groups in terms of information, the PechaKucha technique can be used for topics that nurse educators want to draw particular attention to.
Keywords: PechaKucha; Nursing education; Power Point presentation